The Mediating Role of Subjective-Wellbeing in Terms of Perceived Stress and Hypertension - Farrokh Haghranjbar; Mahboube Shirzad; Mohamad Hosein Taghdisi; Gholam Reza Sarami; Hasan Ahadi (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Hypertension is a psycho-physiological problem. There are several biological and psychological factors that affect the incidence and severity of hypertension. The present study was aimed to investigate the mediating role of subjective-wellbeing in terms of perceived stress and hypertension. Materials and methods: In this descriptive-correlated study, the study population included over-45-adult patients with hypertension who referred to health centers in Tehran. Through convenience sampling 298 persons (121 male and 177 female) were selected as samples of the study. Perceived stress scale questionnaire and subjective well-being questionnaire were used to gather the data. To analyze the data Structural equation modeling (SEM) was used. Results: There was a significant and negative correlation between subjective well-being and hypertension (p < 0.01, β = 0.353). The subjective well-being mediates the relationship between perceived stress and hypertension (p < 0.01, β = 0.203) and scores of perceived stress and subjective well-being explain the percentage of variance in blood pressure and changes in scores of perceived stress explain 45% of variance in subjective well-being. Conclusion: People with high blood pressure have high perceived stress and subjective well-being contributes to the control of hypertension. Paper Type: Research Article.